Difficulty level in preparing elemental cost analysis among quantity surveying students in UiTM Perak / Ahmad Azmin and Mohammad Nasharudine Shuib - Azmin, Ahmad; Shuib, Mohammad Nasharudine (2018)
Quantity Surveyor (QS) is a professional in construction cost management, procurement, contractual issues, and infrastructure. Elemental Cost Analysis (ECA) is one of the scope that QS students will learn and use it in the industry as a method of estimating the cost of construction. However, QS students in UiTM Perak have encountered a problem in their implementation of ECA method in the construction economic subject. The aim of this research is to identify what is the main problem that can make the ECA is one of the hard subjects, to learn and why the problem is caused causes and how to overcome it. The techniques used in this research is by distributing questionnaires to to a number of 60 part 6 students of UiTM Perak taking Diploma in Quantity Surveying. The research objectives are to identify what will be the Difficulty level of preparing ECA method, to identify the factors that influence UiTM QS students and to examine the steps to improve skills in preparing ECA method.